Analisis Faktor-Faktor Yang Mempengaruhi Impor Minyak Bumi Di Indonesia Tahun 1996-2015 - Dewi, Made Ayu Julia Kusuma; Sudirman, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 7, Juli 2017 (pp. 1157 - 1394), 2017)
The purpose of this study was to analyze the influence of variables prices, foreign exchange rates, and foreign exchange reserves simultaneously and partially on oil imports in Indonesia. Object of this research is the price, foreign exchange rates, and foreign exchange reserves to import oil in Indonesia in 1996-2015. This research was conducted in the country of Indonesia. The types of data used in this research is secondary data or time series. Data were analyzed using multiple linear regression. Based on the results of data analysis found that simultaneous variable prices, foreign exchange rates, and foreign exchange reserves significantly influence oil imports in Indonesia. Partial variable prices are not negative and not significant to oil imports. In partial foreign exchange rates are not a significant negative effect on petroleum imports, and foreign exchange reserves variable positive and significant impact on oil imports in Indonesia.
Keywords: impor minyak bumi, harga, kurs valuta asing, cadangan devisa.